The taxonomic status of Tantilla marcovani Lema 2004 (Squamata: Colubridae) - Mata-Silva, Vicente; Wilson, Larry David (Zootaxa, 2016)
The colubrid snake genus Tantilla currently comprises 62 valid species distributed from the southern United States of America to southern Bolivia in the west, and Uruguay and northern Argentina in the east (Wilson & Mata-Silva 2014, 2015). Of these 62 species, 13 are found in South America (Wilson & Mata-Silva 2014, 2015). The most recently described of these Southamerican species is Tantilla marcovani Lema, 2004. While we were working on a checklist and key to the members of the Tantilla clade (sensu Holm 2008, including the genera Geagras Cope 1876, Scolecophis Fitzinger 1843, Tantilla Baird & Girard 1853, and Tantillita Smith 1941; Wilson & Mata-Silva 2015), it became apparent that the diagnosis of T. marcovani entirely falls to distinguish this nominal taxon from the widespread and extensively variable T. melanocephala Linnaeus 1758. Tantilla melanocephala, as presently envisioned, is the most broadly distributed member of its genus (Wilson & Mena 1980; Savage 2002; Greenbaum et al. 2004), occurring from Panama southward into the major portion of the South American continent, apart from Chile and southern Argentina.